Guest

3(2x – 3) = 4(2x + 4) 3(2x – 3) = 4(2x + 4) 3(2x – 3) = 4(2x + 4) 3(2x – 3) = 4(2x + 4) 3(2x – 3) = 4(2x + 4) 3(2x – 3) = 4(2x + 4)

3(2x – 3) = 4(2x + 4)
3(2x – 3) = 4(2x + 4)
3(2x – 3) = 4(2x + 4)
3(2x – 3) = 4(2x + 4)
3(2x – 3) = 4(2x + 4)
3(2x – 3) = 4(2x + 4)

Grade:12

1 Answers

Harshit Singh
askIITians Faculty 5964 Points
one year ago
Dear Student

3(2x – 3) = 4(2x + 4)

6x – 9 = 8x + 16

6x – 8x = 16 + 9

-2x = 25

x = -25/2

Thanks

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free